Development of an algorithm for phenotypic screening of carbapenemase-producing Enterobacteriaceae in the routine laboratory - Robert, Jérôme (BMC Infect Dis, 2017)
BACKGROUND: Carbapenemase-producing Enterobacteriaceae (CPE) are difficult to identify among carbapenem non-susceptible Enterobacteriaceae (NSE). We designed phenotypic strategies giving priority to high sensitivity for screening putative CPE before further testing. METHODS: Presence of carbapenemase-encoding genes in ertapenem NSE (MIC > 0.5 mg/l) consecutively isolated in 80 French laboratories between November 2011 and April 2012 was determined by the Check-MDR-CT103 array method. Using the Mueller-Hinton (MH) disk diffusion method, clinical diameter breakpoints of carbapenems other than ertapenem, piperazicillin+tazobactam, ticarcillin+clavulanate and cefepime as well as diameter cut-offs for these antibiotics and temocillin were evaluated alone or combined to determine their performances (sensitivity, specificity, positive and negative likelihood ratios) for identifying putative CPE among these ertapenem-NSE isolates. To increase the screening specificity, these antibiotics were also tested on cloxacillin-containing MH when carbapenem NSE isolates belonged to species producing chromosomal cephalosporinase (AmpC) but Escherichia coli. RESULTS: Out of the 349 ertapenem NSE, 52 (14.9%) were CPE, including 39 producing OXA-48 group carbapenemase, eight KPC and five MBL. A screening strategy based on the following diameter cut offs, ticarcillin+clavulanate <15 mm, temocillin <15 mm, meropenem or imipenem <22 mm, and cefepime <26 mm, showed 100% sensitivity and 68.1% specificity with the better likelihood ratios combination. The specificity increased when a diameter cut-off <32 mm for imipenem (76.1%) or meropenem (78.8%) further tested on cloxacillin-containing MH was added to the previous strategy for AmpC-producing isolates. CONCLUSION: The proposed strategies that allowed for increasing the likelihood of CPE among ertapenem-NSE isolates should be considered as a surrogate for carbapenemase production before further CPE confirmatory testing. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12879-016-2174-y) contains supplementary material, which is available to authorized users.